2005
DOI: 10.1074/jbc.m413269200
|View full text |Cite
|
Sign up to set email alerts
|

Calpain I Induces Cleavage and Release of Apoptosis-inducing Factor from Isolated Mitochondria

Abstract: The translocation of apoptosis-inducing factor (AIF) from mitochondria to the nucleus has been implicated in the mechanism of glutamate excitotoxicity in cortical neurons and has been observed in vivo following acute rodent brain injuries. However, the mechanism and time course of AIF redistribution to the nucleus is highly controversial. Because elevated intracellular calcium is one of the most ubiquitous features of neuronal cell death, this study tested the hypothesis that cleavage of AIF by the calcium-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
318
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(335 citation statements)
references
References 55 publications
15
318
2
Order By: Relevance
“…Indeed, AIF needs to be cleaved for becoming a soluble and apoptogenic protein (Otera et al, 2005). Recent studies in isolated mitochondria have shown that AIF cleavage is caspase-independent and involves specific cysteine proteases like calpain I or cathepsins B, L and S (Polster et al, 2005;Yuste et al, 2005). Here, we show that calpain inhibition not only decreases A3D8-induced cell death but also inhibits AIF translocation suggesting that AIF release from mitochondria may be a direct consequence of calpain activity in HEL cells.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cellsmentioning
confidence: 48%
See 2 more Smart Citations
“…Indeed, AIF needs to be cleaved for becoming a soluble and apoptogenic protein (Otera et al, 2005). Recent studies in isolated mitochondria have shown that AIF cleavage is caspase-independent and involves specific cysteine proteases like calpain I or cathepsins B, L and S (Polster et al, 2005;Yuste et al, 2005). Here, we show that calpain inhibition not only decreases A3D8-induced cell death but also inhibits AIF translocation suggesting that AIF release from mitochondria may be a direct consequence of calpain activity in HEL cells.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cellsmentioning
confidence: 48%
“…Finally, and because it has recently reported that calpain I can induce cleavage and release of AIF from isolated mitochondria (Polster et al, 2005), we examined whether calpain inhibition could affect AIF release observed during A3D8-induced cell death. Treatment with the calpain inhibitor calpeptin (Figure 7d) efficiently decreased AIF nuclear translocation in A3D8-treated HEL cells.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cells C Artus Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Once relocalized to the cytosol, cytochrome c activates caspase-9 by binding its regulatory subunit Apaf-1, a AAA ATPase-related protein with a C-terminal WD repeat protein (Li et al, 1997;Yu et al, 2005). Additional pro-death factors that are released from mitochondria (e.g., AIF, SMAC/Diablo, Omi/Htr2A) were reported to activate both caspase-dependent and caspase-independent death programs, though controversies remain (Foghsgaard and Jaattela, 1997;Jaattela, 2002;Garrido and Kroemer, 2004;Saelens et al, 2004;Polster et al, 2005). This mitochondrial outer membrane permeabilization (MOMP) occurs by an unknown biochemical mechanism that requires one or both of the pro-death multidomain Bcl-2 family proteins Bax and Bak (Hardwick and Polster, 2002;Green and Kroemer, 2004).…”
Section: The Executioner Mitochondrionmentioning
confidence: 99%
“…Indeed, AIF is a flavoprotein that can oxidize NADH and NADPH in vitro (Miramar et al, 2001) and may participate in the detoxification of reactive oxygen species (Klein et al, 2002) and in the maintenance of glutathione levels (Cande et al, 2004b), although the mechanisms of this antioxidant activity remain to be determined. Upon activation of a serine protease that liberates AIF from its membrane attachment (Polster et al, 2005;Yuste et al, 2005), combined with outer mitochondrial membrane permeabilization, for instance through Bax/Bak-mediated pores (Green and Kroemer, 2004), AIF is released from mitochondria and participates in the catastrophic catabolic process that allows the digestion of the cellular content from within.…”
Section: Introductionmentioning
confidence: 99%